The Shifting Nature of Academic Library Collections - Way, Doug (University of Wisconsin-Madison, 2017)
Academic libraries exist in a changing world full of challenges. Many of the changes and the challenges they present are out of our control. These challenges include things like hyperinflation. Journal prices today continue to rise at a rate that far out-strips traditional inflation measures, such as the Consumer Price Index, creating tremendous on library budgets. There has also been a steady increase in research and development spending in the United States. This is directly correlated with an increase in the number of journals published each year. Both of these increases easily outstrip any increases in library budgets.
Keywords: academic library; library collection; collection management; collection development; Research Subject Categories::SOCIAL SCIENCES::Other social sciences::Library and information science